1989
DOI: 10.1108/eum0000000002490
|View full text |Cite
|
Sign up to set email alerts
|

Service Pricing: a Differentiation Premium Approach

Abstract: States that current pricing strategies used in the service industries are often too simplistic and ineffective in the face of complex environmental conditions. Introduces the Pricing Differentiation Premium Model, which includes in the firm′s pricing strategy its ability to differentiate itself from competitors. Discusses possible strategies for influencing differentiation premiums which can improve the pricing discretion of the service provider.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…First, since traditional pricing strategies were developed for products, they capture product costs more accurately and prices are built on such costs (Schlissel & Chasin, 1991). These strategies can be adapted for services as well since the common elements of understanding customer value, provider costs and competition remain relevant for services as well (Arnold, Hoffman, & McCormick, 1989;Indounas, 2009;Schlissel & Chasin, 1991). However, integrated solutions represent more of a paradigm shift.…”
Section: Pricing Solutions: a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…First, since traditional pricing strategies were developed for products, they capture product costs more accurately and prices are built on such costs (Schlissel & Chasin, 1991). These strategies can be adapted for services as well since the common elements of understanding customer value, provider costs and competition remain relevant for services as well (Arnold, Hoffman, & McCormick, 1989;Indounas, 2009;Schlissel & Chasin, 1991). However, integrated solutions represent more of a paradigm shift.…”
Section: Pricing Solutions: a Reviewmentioning
confidence: 99%
“…Third, in product pricing that is influenced by the competition, it is assumed that customer can compare products and determine the value of various competitive offerings (Anderson & Wynstra, 2010;Berry & Yadav, 1996). However, since the true solutions provider designs the customized solution after customer needs are determined for each customer, competitive considerations may appear only when obtaining the customer's business and not when pricing the solution prior to its development (Arnold et al, 1989).…”
Section: Pricing Solutions: a Reviewmentioning
confidence: 99%
“…Cost based pricing and competition driven pricing are commonly used in practice and have became the mainstream pricing techniques. However, the simplified characteristics may lose its effectiveness in complex and competitive operating environments (Arnold et al, 1989). The main disadvantage of cost based pricing is that the unit costs are difficult to access and may result in overpricing or under-pricing problems (Collins and Parsa, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Criticality of service: Previous research (Hoffman, 1989) has shown that the more "essential" the service, the higher the price demanded by the provider. Similarly, previous findings suggest that the more involved consumers are in a particular service purchase, the more insensitive they are toward price information (Gotlieb et al, 1987).…”
Section: Service Intrinsic Factorsmentioning
confidence: 99%